The Effect of Liquidity, Company Size, Leverage, and Company Age on Profitability (Case Study on Telecommunication Company) - Sabilillah, Restu Ajeng; Rahayu, Sri; Suryatama, Fajar (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the effect of liquidity, leverage, firm size, and firm age on profitability, with a case study of telecommunications companies listed on the Indonesia Stock Exchange. The telecommunications industry is characterized by rapid technological development and intense competition, which requires firms to manage their financial resources efficiently in order to maintain sustainable profitability. This research employs a quantitative approach using secondary data obtained from annual financial statements over a five-year observation period. The sample is selected through purposive sampling, and the data are analyzed using multiple linear regression supported by classical assumption testing. The results indicate that liquidity and firm size have a significant effect on profitability, suggesting that effective management of short-term assets and an optimal scale of operations contribute positively to financial performance. In contrast, leverage and firm age do not show a significant influence on profitability, indicating that higher debt levels and longer operational experience do not necessarily increase profit generation in telecommunications firms. Overall, the findings highlight the importance of internal financial efficiency in improving profitability. This study provides valuable insights for corporate management and investors in formulating sound financial strategies within the telecommunications sector.